2014
DOI: 10.1111/anae.12532
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing short‐ and long‐term mortality after lower limb amputation

Abstract: SummaryMortality after lower limb amputation is high, with UK 30-day mortality rates of 9-17%. We performed a retrospective analysis of factors affecting early and late outcome after lower limb amputation for peripheral vascular disease or diabetic complications at a UK tertiary referral vascular centre between 2003 and 2010. Three hundred and thirty-nine patients (233 male), of median (IQR [range]) age 73 (62-79 [26-92]) years underwent amputation. Thirty-day mortality was 12.4%. On regression modelling, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
5
42
0
Order By: Relevance
“…2,[5][6][7][8]11,13,[23][24][25] We also observed a high mortality rate of 10.8% in the present study. LLA is often performed as a life-saving measure for a critically ischemic or infected limb in patients with DM or PVD.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…2,[5][6][7][8]11,13,[23][24][25] We also observed a high mortality rate of 10.8% in the present study. LLA is often performed as a life-saving measure for a critically ischemic or infected limb in patients with DM or PVD.…”
Section: Discussionsupporting
confidence: 78%
“…These findings are consistent with those in previous studies. 2,[7][8][9]11,23) Little is known about reamputation following LLA, and the present study is the largest study of its kind. Reamputation occurred in 10.1% of patients who underwent foot or transtibial amputation during hospitalization.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Firstly, pre-operative septic shock, ASA 4 status and site of amputation of AKA are significant predictors of higher post-operative in hospital mortality rate and ICU admission. Previous studies evaluating non-traumatic MLEA found thatage, 6 albumin level, 6 AKA, 4,6 lack of a previous coronary artery bypass graft, 6 renal insufficiency, 4 ASA grade ≥4 12 and out-of-hours surgery 12 are factors that affect peri-operative mortality rate. This knowledge is important when risk stratifying patients before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is mixed evidence in the literature when evaluating whether anaesthesia technique affects mortality rate in MLEA surgeries. One study found that the type of anaesthetic (neuraxialvs general) was not associated with survival when corrected for other variables, 12 while other studies show that avoiding general anaesthesia in favour of regional anaesthesia may improve post-operative outcomes in non-traumatic MLEA surgeries. 7,16 However, all these studies did not distinguish between central neuraxial block and peripheral nerve block in the group analysed under regional anaesthesia.…”
Section: Discussionmentioning
confidence: 99%